CRITICAL LOOK AT THE CUBAN HISTORIOGRAPHY CONCERNING THE MARGINALITY OF THE BLACK IN THE LIBERATING ARMY (Tzintzun, Revista de Estudios Históricos, 2016)
In this look at the Cuban historiography concerning the marginality of theblack in the liberating army, the most significant works that approach thisproblematic in Cuba are analyzed. There is revealed that today, after 115years of the beginning of the independence exploit, it continues withoutexisting a complete corpus of this phenomenon that gathers the socialbehavior during the whole warlike contest (1868-1898) and that is centredby on the rebellious army. In addition, the study noticed that the marginality,the discrimination and the racism - between the most marked inheritanceswith the slavery and with the culture that from this one begins in Cuba -was a problem that, though it also affected certain leaders of black race, forthe most part it harmed to the most deprived rebellious blacks, and due tothis it was more difficult to detect, exemplify and consider as a problem thatexisted in the rows of the Cuban revolutionaries. Finally, it is made arecommendation on how to channel the analysis of this still in forceproblematic in the black population in Cuba, interlacing the different sociallinks that join it.
Keywords: Cuba; historiography; independence war; rebellious army; marginality of the blacks